New low‐ε r, temperature stable Mg3B2O6‐Ba3(VO4)2 microwave composite ceramic for 5G application. Issue 8 (16th April 2021) - Zhou, Tao; Liu, Yahan; Song, Kaixin; Xue, Lingyun; Xu, Ping; Khesro, Amir; Wang, Dawei; Liu, Bing; Mao, Minmin; Shi, Feng; Sun, Shikuan
Abstract: Novel low‐ εr, thermal and phase stable of (1‐x)Mg3 B2 O6 ‐xBa3 (VO4 )2 (x mol% =51, 53, 55, 57, 59) microwave composite ceramics were firstly fabricated and reported using the conventional solid‐state reaction method. X‐ray diffraction, scanning electron microscopy, energy dispersive X‐ray, and Raman spectroscopy confirmed the coexistence of both phases without other phases. Near‐zero temperature coefficient of resonant frequency ( τf +1.2 ppm/°C) is obtained for the 0.43Mg3 B2 O6 ‐0.57Ba3 (VO4 )2 composite ceramic, with permittivity ( εr ) of 8.8 and high‐quality factor ( Q × f ) of 45 420 GHz, which is a promising candidate for 5G applications.